Macrophytes in Aquatic Ecosystems: From Biology to Management
DOI: 10.1007/978-1-4020-5390-0_25
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of macrophyte species occurrence in Swiss ponds

Abstract: The study attempted to model the abundance of aquatic plant species recorded in a range of ponds in Switzerland. A stratified sample of 80 ponds, distributed all over the country, provided input data for model development. Of the 154 species recorded, 45 were selected for modelling. A total of 14 environmental parameters were preselected as candidate explanatory variables. Two types of statistical tools were used to explore the data and to develop the predictive models: linear regression (LR) and generalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example Briers and Biggs (2005) found that environmental variation had little effect on pond invertebrate communities found across 102 ponds in Oxfordshire, UK, unless the variation was considerable. For pond plants Edvardsen and Okland (2006a,b) found that both species richness and composition of plants from individual ponds were only weakly related to environmental variables whilst Joye et al (2006) were able to produce robust models of pond plant species’ individual abundance for only 10 of 45 species selected for modelling.…”
mentioning
confidence: 99%
“…For example Briers and Biggs (2005) found that environmental variation had little effect on pond invertebrate communities found across 102 ponds in Oxfordshire, UK, unless the variation was considerable. For pond plants Edvardsen and Okland (2006a,b) found that both species richness and composition of plants from individual ponds were only weakly related to environmental variables whilst Joye et al (2006) were able to produce robust models of pond plant species’ individual abundance for only 10 of 45 species selected for modelling.…”
mentioning
confidence: 99%